Efficacy of Voided Urine Cytology Compared to Cystoscopic Findings in the Detection of Bladder Cancer- A Pakistani Perspective - Khizar, Samina; Mirza, Zahoor Iqbal; Ahmed, Hussain; Murtaza, Badar; Yasrab, Muhammad; Shahzad, Khubaib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of voided urine cytology with findings of cystoscopy and histopathology of biopsy specimens in the diagnosis of bladder cancer.Study Design: Comparative cross-sectional studyPlace and Duration of Study: Armed forces Institute of Urology (AFIU), Rawalpindi Pakistan from Jan 2019 to Jan 2020.Methodology: All patients presenting to the urology clinic with complaints of haematuria, visible and non-visible, and any radiologic evidence of bladder growth were included in the study after informed consent. Urine cytology was performed for all patients, followed by cystoscopy under anaesthesia, transurethral resection was conducted, and biopsy was taken where needed.Results: 170 patients were included in the study134 (78.8%) were males, while 36 (21.2%) were females. The mean age was 54 ± 9.47 years (range 36 to 73 years). The overall sensitivity of voided urine cytology was 46.7%, while specificity was 79.2%. The positive predictive value was 85.1%, and the negative predictive value was 36.9%.Conclusion: Bladder cancer is a disease which demands an early diagnosis, prompt treatment, and long-term follow-up. Cystoscopy remains the gold standard for this purpose; urine cytology can be used as a supplement as it is non-invasive, more specific and cost-effective.